VOICE FROM VOID: SUBALTERN IDENTITY, PSYCHO-CULTURAL SENSIBILITY AND CASTE PARLANCE IN FILM KANTARA - Panicker, Joji John (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The 2022 Kannada-language film Kantara, serves as a compelling exploration of subaltern psychocultural sensibilities within the context of coastal Karnataka’s socio-cultural landscape. This article analyzes how Kantara engages with the subaltern through its portrayal of the Bhuta Kola ritual, caste dynamics, and the tension between tradition and modernity. Drawing on Gayatri Chakravorty Spivak’s concept of the subaltern and Antonio Gramsci’s notion of cultural hegemony, the study examines the film’s representation of marginalized communities, particularly the forest-dwelling tribes and lower-caste groups, and their psychocultural expressions. The narrative’s rootedness in local folklore, coupled with its depiction of land rights and spiritual practices, highlights the agency and resistance of subaltern voices against dominant structures. By weaving together psychoanalytic and postcolonial frameworks, this article uncovers how Kantara negotiates identity, power, and cultural memory, offering a nuanced portrayal of subalternity. The film’s critical and commercial success underscores its relevance in contemporary Indian cinema, where subaltern narratives are increasingly gaining visibility. This analysis contributes to broader discussions on caste, indigeneity, and cultural representation in Indian popular cinema, emphasizing the psychocultural dimensions of subaltern resilience and spirituality.